Evaluating Employee Innovation and Creativity towards Employee Turnover Intention in the Hospitality Industry - Diyana, Kamarudin; Hu, Xiaojie; Yasmin, Hussain; Ling, Yee Kai (Revista Geintec-Gestao Inovacao E Tecnologias, 2021)
Hospitality industry plays a main role and has become a major sector in Malaysia’s economy. However, there are some challenges in the hospitality industry such as employee turnover which could have various consequences to organizations. The purpose of this research is to investigate the factors affecting employee turnover intention, either directly or indirectly. Previous studies have suggested that employee turnover intention could be affected by factors such as leadership, motivation, communication, work environment and infrastructure both directly and indirectly. Employee innovation and creativity as a mediating factor could also affect its relationship with turnover intention of employees. The research design for this study was quantitative research method using questionnaires as the data collection method. Purposive sampling was used to sample 152 hotel employees within the West of Malaysia. Structural Equation Modelling was used to analyze the data using SmartPLS software. Results indicated that leadership, motivation, communication, and work environment and infrastructure had significant relationship with employee innovation and creativity. Apart from that, leadership, motivation and communication also have significant relationship with the employee turnover intention. Turnover is a major issue within companies not only for the company’s sustainability, but also for the health and wellbeing of their employees. As an implication, organizations should understand that their leadership characteristic and environment has a tremendous impact to burnout and employee performance.